2002
DOI: 10.1086/342997
|View full text |Cite
|
Sign up to set email alerts
|

Before and After TANF: The Economic Well‐Being of Women Leaving Welfare

Abstract: Welfare caseloads have fallen dramatically in the last several years, raising questions about the economic well-being of those who left. In this paper we use administrative data from Wisconsin to identify those who left welfare and to provide information on their economic well-being. We provide a context for understanding post-welfare well-being by comparing welfare leavers under early Wisconsin reforms (those who left in the fourth quarter of 1995) with those who left under the later, more stringent TANF prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 5 publications
6
76
1
Order By: Relevance
“…For example, women in Michigan who worked part-time at minimum wage jobs were at the median for monthly net income among 12 states that contained a large portion of the nation's population and about half of the 1998 caseload (Acs et al, 1998). Furthermore, the fraction of women in our sample who are employed, the fraction who have left welfare, and the fraction who have left welfare and are working but do not have employersponsored health insurance, are all very similar to the results of a recent MDRC report on Cleveland (Brock et al, 2002), results in Wisconsin from a study by Cancian et al (2000), and very similar to those reported by Acs and Loprest (2001) at the Urban Institute using administrative data from the Washington, DC area. Because of the similarities in the fraction working across all of these studies, we do not expect our results to differ from those that would be found in other studies if these other studies had measured the same things using the same models.…”
Section: The Michigan Employer Survey (Mes)supporting
confidence: 83%
See 1 more Smart Citation
“…For example, women in Michigan who worked part-time at minimum wage jobs were at the median for monthly net income among 12 states that contained a large portion of the nation's population and about half of the 1998 caseload (Acs et al, 1998). Furthermore, the fraction of women in our sample who are employed, the fraction who have left welfare, and the fraction who have left welfare and are working but do not have employersponsored health insurance, are all very similar to the results of a recent MDRC report on Cleveland (Brock et al, 2002), results in Wisconsin from a study by Cancian et al (2000), and very similar to those reported by Acs and Loprest (2001) at the Urban Institute using administrative data from the Washington, DC area. Because of the similarities in the fraction working across all of these studies, we do not expect our results to differ from those that would be found in other studies if these other studies had measured the same things using the same models.…”
Section: The Michigan Employer Survey (Mes)supporting
confidence: 83%
“…Studies of women who have left AFDC find low-paying jobs to be the norm and little wage growth in the first several years after leaving welfare (Cancian et al, 2000;Harris, 1996;Pavetti, Holcomb, and Duke, 1995;Riccio, Friedlander, and Freedman, 1994). Burtless (1995), using National Longitudinal Survey of Youth (NLSY) data, showed that women with low levels of schooling and low Armed Forces Qualification Test (AFQT) scores had lower rates of wage growth with age than did other women, and conjectured that these low rates of wage growth reflect recipients' low skill levels.…”
Section: Making the Transition From Bad Job To Good Jobmentioning
confidence: 99%
“…In contrast, based on a longitudinal analysis of administrative data, Cancian, Haveman, Meyer, and Wolfe (2000) estimate that annualized income fell by over $2,000 among those leaving welfare in Wisconsin in 1995. Strong increases in earnings and estimates of the EITC were more than offset by decreases in cash assistance and Food Stamps.…”
Section: Household Incomementioning
confidence: 96%
“…Gleason, Schochet, & Moffitt, 1998;Harris, 1996;Hoynes, 2000), and some studies have examined the economic well-being of single mothers who left welfare (Cancian et al, 2002;Cancian & Meyer, 2004;Meyer & Cancian, 1998). But only one study compared the long-term social and economic outcomes of AFDC recipients and nonrecipients (Vartanian & McNamara, 2004), and no previous studies of housing assistance examine the long-term economic outcomes of women.…”
Section: / the Long-term Effects Of Housing Assistance On Work And Wementioning
confidence: 99%